Estrogen receptor-α expressing neurons in the ventrolateral VMH regulate glucose balance - Yanlin He (Nature Portfolio, 2020)
Glucose-sensing neurons are found in the ventromedial hypothalamic nucleus (VMH). Here the authors identify the role of estrogen receptor-α expressing neurons in the ventrolateral subdivision of the VMH in sensing hypoglycemia.